Introduction of chess in preschool childhood: a pedagogical experiment - Pérez Peña, Luis Enrique (Transformación, 2024)
Methods: The pertinence of the descriptors and tools to be used was assessed by expertise interviewing and critical opinion and collective construction workshops. The strategy reliability assessment was completed with a pedagogical experiment (four groups of Solomon) with children of four to five years old attending to preschool centers of following the “Educa a tu Hijo” program at the Camagüey city. Result: The findings revealed significant differences in pre-school chess introduction descriptors in the experimental groups as compared to the control groups, therefore the impact of the pedagogical strategy and the relevance of the experiential-modeling method were confirmed. in the initiation of Chess in the educational process of boys and girls from four to five years. Conclusion: The achievements in the introduction of chess playing in preschool-age suggests the significance of chees initiation a ludic possibility in the educational process of preschool education.